Deception Under Time Pressure: Conscious Decision or a Problem of Awareness? - Kai A. Konrad; Tim Lohse; Sven A. Simon (Center for Economic Studies and ifo Institute (CESifo), 2017)
Time is a crucial determinant of deception, since some misreporting opportunities come as a surprise and require an intuitive decision while others allow for extensive reflection time. To be able to pursue a deceptive strategy, however, a subject must be aware of the misreporting opportunity. This paper provides experimental evidence on the role of the time dimension for dishonest decision-making and for the cognition process of the chance to deceive. We conduct a laboratory experiment of self-serving deceptive behavior which combines two exogenously varied levels of reflection time with a cognition process about the deception opportunity. We find that time pressure leads to more honesty compared to sufficient contemplation time. More importantly, decomposing misreporting into its two components, i.e., the cognition process of the misreporting opportunity and the conscious decision to misreport, reveals that more reflection time increases awareness of the misreporting opportunity. However, more time has no effect on the conscious decision of whether to misreport or not. Due to subjects' lack of awareness under time pressure we conclude that honesty is the intuitive response.
Keywords: C91; D83; K42; 330; time pressure; awareness; deception; contemplation; cognitive process; laboratory experiment